Social media addiction scale-adult form: reliability generalization meta-analysis - Doğan, İsmailcan (Journal of Dependence, 2024)
Objective: Social media addiction is an important problem that has been the subject of many studies. When the literature is examined, researchers have developed different scales and conducted research on the subject. With the scales developed, the issue has been approached from different perspectives and opinions on the causes, effects and solution suggestions of social media addiction have been presented and continue to be presented. In the domestic literature, one of the scales frequently used by researchers on social media addiction is the "Social Media Addiction Scale - Adult Form (SMADES)". The aim of the study is to general-ize the reliability of the SMA-AAD scale and to reveal the mean value. Method: In this study, the reliability generalization analysis of the SMBS-ADF scale, which is a scale frequently used by researchers on different samples in the literature, was performed and the results were reported. In this context, 58 studies reporting Cronbach's alpha value were included in the study. This value was transformed by Bonett's method. Results: In the study in which the random effects model was used, the average value was observed as 0.8712. Conclusion: In moderator analyses, analogue ANOVA and meta regression analyses were applied separately on categorical and continuous variables. The results were not statistically significant.
Keywords: Social media; addiction; reliability generalization; meta-analysis